The Making of Law in Indonesia: A Criticism and Evaluation of The Practise of Legislative Function in The House of Representatives - Siti Mariyam; Adhi Putra Satria; Markus Suryoutomo (PROGRAM STUDI MAGISTER ILMU HUKUM FAKULTAS HUKUM UNIVERSITAS DIPONEGORO SEMARANG, 2020)
The House of Representatives is a state institution that functions in the field of legislation. The current fact is that the DPR's performance in the field of legislation always gets records, because the resulting Law is still below Prolegnas target. On the basis of the problems as referred to, the writing of this article aims to find out what the problems and the efforts that need to be made in overcoming the problem of the formation of laws which fall under the authority of the DPR are. In the discussion, the author tries to provide criticism aimed at the process of forming a law in the DPR, seen from three indicators, namely from the legal substance factor, the legal structure factor and the legal culture factor, the legal substance relating to the current Law does not regulate the maximum number of Prolegnas, the legal structure related to law-forming institutions originating from political parties, and the legal culture related to community rejection of the bill being discussed. The solution to these 3 (three) problems needs to be changed, such as strengthening regulations regarding restrictions on performance-based Prolegnas submissions, making Integrity Facts for DPR members and regulations governing public involvement in making laws stronger, this needs to be done in order to keep it up. maintain the level of public trust in the DPR in carrying out its legislative functions.